Intraoperative left atrial dissection following mitral valve surgery: Report of a case treated surgically. Issue 12 (2nd November 2022) - Matteucci, Matteo; Torchio, Federica; Messina, Corinne; Inzigneri, Giovanna; Severgnini, Paolo; Musazzi, Andrea
Abstract: Left atrial dissection (LatD) is an exceedingly rare but serious complication of cardiac surgery. Its clinical presentation is very different in individual cases. Surgical treatment for LatD is often selected when the patient is hemodynamically unstable; conservative treatments are commonly employed under stable conditions. We report a case of LatD after mitral valve replacement that was treated surgically with creation of an atrial fenestration.